Dictionary of word origins - Flavell, Linda; Flavell, Roger (London Kyle Cathie Limited, 2010)
"Words are the building blocks of language, but their derivations are often stories in themselves. Have you ever wondered why we tread gingerly, use cliche, work on our stamina, speak in jargon? With entries from antelope to zoo and including such disparate items as blackmail, fiasco, influence and rigmarole, Dictionary of Word Origins explains the origins and development of over 300 commonly used words. Essays scattered throughout the book deal with more general topics such as 'a taste of India', 'days of the week' and 'precise timing'." -- Provided by publisher
Published in paperback 1994 ; Revised edition published 2008.
Includes bibliographical references (pages 313-314) and index.
Keywords: English language -- Etymology -- Dictionaries